Regimes of Mobility Borders and State Formation in the Middle East, 1918-1946 - Tejel, Jordi; Ramazan Hakkı Öztan (Edinburgh University Press, 2023)
For the past two decades, insights gained from the burgeoning field of borderlands studies have enabled a new generation of scholars to challenge popular depictions of the emergence of the modern Middle East. For them, the region's borderlands were not just mere sites of peripheral activity, but rather liminal spaces criss-crossed by global flows and circulations central to state- and nation-formation across the Middle East. Regimes of Mobility offers a select number of case studies that highlight the connectedness of the politics of borderlands throughout the interwar Middle East. The emergence of the modern Middle East is the result of three complementary historical developments: the disintegration of the Ottoman Empire, the institution of British and French control in its stead and the nationalist challenges to this colonial scramble. The introduction of international borders that accompanied this process is commonly portrayed as the drawing of lines in the sand, an artificial partitioning that brought diplomatic closure to an otherwise contested historical space.